The reinterpretation of Maqasid al-Shari'ah (A study on Jasser Auda's Thought and its Significance in Developing the Methodology of Qur'anic Tnterpretation) - Akhmad Mughzi Abdillah (Fak. Ushuluddin, Studi Agama dan Pemikiran Islam UIN Sunan Kalijaga, 2013)
har,1/rt